2023
DOI: 10.1002/fft2.272
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside CK inhibits androgenetic alopecia by regulating Wnt/β‐catenin and p53 signaling pathways in AGA mice

Abstract: Androgenetic alopecia (AGA) is one of the most common chronic skin diseases caused by the destruction of androgens in the body. It is caused by the excessive deposition of dihydrotestosterone around the hair follicle, resulting in hair follicle atrophy and hair cell apoptosis. It causes great anxiety and psychological distress to patients and affects sexual function in severe cases. As traditional Chinese herbs, ginsenosides have been proven to possess various pharmacological activities. Ginsenoside CK is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Fang et al examined ginsenoside CK for cytotoxicity at various concentrations (0.2–10.0 μM). They observed that CK concentrations below 10 μM had no discernible impact on the survival rate of HaCaT keratinocyte cells [ 28 ]. The osteoblastic cell line MC3T3-E1 was exposed to CK at various concentrations (0.1–10 μM) and did not exhibit any appreciable toxicity [ 8 ].…”
Section: Pharmacokinetics Safety and Toxicological Studies Of Ck And ...mentioning
confidence: 99%
“…Fang et al examined ginsenoside CK for cytotoxicity at various concentrations (0.2–10.0 μM). They observed that CK concentrations below 10 μM had no discernible impact on the survival rate of HaCaT keratinocyte cells [ 28 ]. The osteoblastic cell line MC3T3-E1 was exposed to CK at various concentrations (0.1–10 μM) and did not exhibit any appreciable toxicity [ 8 ].…”
Section: Pharmacokinetics Safety and Toxicological Studies Of Ck And ...mentioning
confidence: 99%
“…Fang et al examined ginsenoside CK for cytotoxicity at various concentrations (0.2-10.0 µM). They observed that CK concentrations below 10 µM had no discernible impact on the survival rate of HaCaT keratinocyte cells [28]. The osteoblastic cell line MC3T3-E1 was exposed to CK at various concentrations (0.1-10 µM) and did not exhibit any appreciable toxicity [8].…”
Section: Pharmacokinetics Safety and Toxicological Studies Of Ck And ...mentioning
confidence: 99%
“…Within traditional Chinese medicine, ginseng stands as a rare herb renowned for its exceptional properties. It is characterized by its remarkable therapeutic efficacy, gentle nature, minimal side effects, and high level of safety, endearing it to practitioners in healthcare and various other domains (Fang et al, 2023). Ginseng holds profound significance within traditional Chinese herbal medicine systems (Ren et al, 2023).…”
Section: Introductionmentioning
confidence: 99%